Synthesis of full-length homodimer αD-VxXXB that targets human α7 nicotinic acetylcholine receptors. Issue 11 (15th September 2022) - Ho, Thao N. T.; Abraham, Nikita; Lewis, Richard J.
Abstract : αD-VxXXB is a homodimer of paired 50-residue peptide with ten conserved cysteines. Here we reported the first synthetic approach to full-length VxXXB via α-ketohydroxylamine ligation that enables further characterisation of this novel class of allosteric nAChR inhibitors. Abstract : αD-Conotoxin VxXXB is a pseudo-homodimer that allosterically inhibits nicotinic acetylcholine receptors (nAChRs) with high potency and selectivity. However, challenges in synthesizing αD-conotoxins have hindered further structure–function studies on this novel class of peptides. To address this gap, we synthesized and characterized its C-terminal domain (CTD) and N-terminal domain (NTD). The CTD inhibited α7 nAChRs (IC50 of 23 nM, measured via FLIPR assays) and bound at the acetylcholine binding protein ( Ls -AChBP) through an allosteric binding mode determined from radioligand binding assays. The anti-parallel dimeric NTD synthesised via a regioselective strategy also inhibited α7 nAChRs but with reduced potency (IC50 of 30 μM). The α-ketoacid-hydroxylamine (KAHA) method generated CTD linked to the NTD (VxXXB-NC; α7 IC50 of 27 nM) and full-length synthetic VxXXB variant (α7 IC50 of 11 nM), while the three other native chemical ligation approaches proved unsuccessful. This work underpins further characterisation of the structural components contributing to αD-conotoxin affinity, selectivity and allosteric inhibition of nAChR function that may prove useful in the development of new treatments for nAChR-related disorders.